Genome-wide association study and heritability estimate for ectopic ureters in Entlebucher mountain dogs - Gallana, M.; Utsunomiya, Y. T. [UNESP]; Dolf, G.; Pintor Torrecilha, R. B. [UNESP]; Falbo, A. K.; Jagannathan, V.; Leeb, T.; Reichler, I.; Sölkner, J.; Schelling, C. (Wiley, 2018)
An ectopic ureter is a congenital anomaly which may lead to urinary incontinence and without a surgical intervention even to end-stage kidney disease. A genetic component contributes to the development of this anomaly in Entlebucher mountain dogs (EMD); however, its nature remains unclear. Using the Illumina CanineHD bead chip, a case–control genome-wide association study was performed to identify SNPs associated with the trait. Six loci on canine chromosomes 3, 17, 27 and 30 were identified with 16 significantly associated SNPs. There was no single outstanding SNP associated with the phenotype, and the association signals were not close to known genes involved in human congenital anomalies of the kidney or lower urinary tract. Additional research will be necessary to elucidate the potential role of the associated genes in the development of ectopic ureters in the EMD breed.
Keywords: Canis lupus familiaris; congenital anomalies of the kidney and urinary tract; congenital anomalies of the lower urinary tract; congenital urological malformation; genome-wide association study; urinary tract development